Improving the performance of China's urban water utilities - Browder, Greg J. (The World Bank, 2007)
As China transitions to a market economy, municipal utilities are evolving into commercially viable companies under government oversight. Great challenges confront the reform process for China's water utilities, including rapid urbanization and emerging inequality, coupled with severe water scarcity and degradation. Cities and their water utilities must provide services within a complex mosaic of policies and regulations provided by national and provincial governments. In China, as throughout the world, water is also a sensitive political issue. Governments are keen to provide good water service, but also attuned to the need to ensure that tariffs are socially acceptable. This report presents a strategic framework and set of recommendations for addressing these challenges and accelerating improvements in China's urban water utilities. Drawing upon the World Bank's experience in China, as well as the Bank's global knowledge, the report provides a comprehensive assessment of urban water services, including policy, regulatory, institutional, financial, and technical issues. The report will prove a valuable resource for policy makers, utility companies, and anyone interested in the development of the world's largest water market.